2015
DOI: 10.1111/jai.12798
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hematological parameters and blood cells of cultured Gymnocypris eckloni Herzenstein, 1891

Abstract: The objective of the study was to obtain baseline data on haematological parameters, blood cell sizes and morphology in cultured male and female Gymnocypris eckloni Herzenstein, 1891. Forty-eight healthy 3-year-old G. eckloni (26 males: 525.79 AE 48.56 g weight, 34.51 AE 1.88 cm total length; 22 females: 507.60 AE 54.48 g weight, 33.97 AE 1.84 cm total length) were used for this study. Both male and female gonadal maturity were at stage III (maturing). The fish were reared in 25-36 m 2 outdoor tanks at dissolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
(46 reference statements)
2
23
0
Order By: Relevance
“…Motlagh et al () had found sex‐dependent differences for WBC, lymphocyte, and heterophil counts in Betta splendens . In Gymnocypris eckloni (Tang et al ), RBC, Hb, HCT, and MCV values in females were significantly lower than those in males among all tested hematological parameters. In S. davidi observed in this study, RBC, WBC, and MCHC counts were significantly higher in females than in males, while MCV were significantly lower in females than in males.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Motlagh et al () had found sex‐dependent differences for WBC, lymphocyte, and heterophil counts in Betta splendens . In Gymnocypris eckloni (Tang et al ), RBC, Hb, HCT, and MCV values in females were significantly lower than those in males among all tested hematological parameters. In S. davidi observed in this study, RBC, WBC, and MCHC counts were significantly higher in females than in males, while MCV were significantly lower in females than in males.…”
Section: Discussionmentioning
confidence: 95%
“…The values of RBC and Hb in S. davidi were high when compared with another schizothoracine fish, G. eckloni (Tang et al ) (Table ). It has been reported that the number of erythrocytes has a positive relationship with fish's athletic capacity (Cao and Wang ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Until now, it has been popularly cultured in the southwest area of China. We have previously characterized G. eckloni blood cells in light microscope, tentatively identifying three populations of blood cells: erythrocytes, leucocytes (heterophils, eosinophils, lymphocytes, monocytes) and thrombocytes (Tang et al, 2015). However, the ultrastructure and cytochemistry of peripheral blood of G. eckloni are currently unknown.…”
Section: Introductionmentioning
confidence: 98%